The relationship of secretory phospholipase A2 type IIA levels with glomerulus filtration rate in type 2 DM patients - Nadifa Kartika Dewi; Mila Citrawati; Dhigna Luthfiyani; Harli Amir Mahmudji (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2020)
Phospholipase/sPLA2 type IIA is a mediator that connects the pathogenesis of diabetes and its complications. Diabetic nephropathy is the most frequent microvascular complication, with albumin urine and changes in glomerular filtration rate. This study aimed to discover the relation between sPLA2 type IIA levels in diabetic patients with glomerular filtration rate (GFR). This study used the crossectional method in 62 samples in RSJ. Prof. Dr. Soerojo Magelang. Sampling was done by total sampling, and medical records were used as an instrument. This research was conducted in patients with sPLA2 type IIA levels and had complete laboratory examination data in 2016. The results showed that the level of sPLA2 type IIA was very high in diabetic patients, and GFR was below standard. Pearson correlation analysis showed no significant correlation between type IIA sPLA2 and GFR (p=0.318), with a positive but weak correlation (r=0.129) with the diabetic duration of 8 years. Pearson correlation analysis was conducted in 21 samples in which GFR values were ≤60 (p=0.0712), resulting in a negative direction (r=-0.086) with a diabetes duration of 11 years. It was shown that diabetic patients with increased levels of sPLA2 type IIA and more extended periods of diabetes would affect the decrease in GFR value.